Three new records of Annonaceae for the flora of Laos - Nagahama, Ai; Tagane, Shuichiro; Souladeth, Phetlasy; Tanaka, Nobuyuki; Yahara, Tetsukazu (Thai Forest Bulletin (Botany), 2024)
Three species of Annonaceae, Dasymaschalon acuminatum, Fissistigma maclurei and Monoon jucundum, from Bolaven Plateau in southern Laos, are reported as new additions to the flora of Laos. Voucher specimens, photographs, geographical distribution, ecology and taxonomic notes are provided for each species.